THE EFFICATION OF AEDES AEGYPTI BIOLARVASIDA GRANUL FROM ETIL ACETAT EXTRACT OF MARSH FLEABANE LEAVES - Agus Rochmat; Mita Napitasari; Afdwiyarni Metta Karina (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
This study was aimed at determining the activity of Marsh Fleabane leaves extract against Aedes aegypti mosquito larvae mortality. Marsh Fleabane leaves extract was obtained using ethanol solvent. After obtaining the viscous extract, the extract was fractionated with solvent n-hexan and ethyl acetate. The ability of this biolarvaside was determined by LC50 value and reinforced by identifying of active compound content. This biolarvaside test was conducted on Aedes aegypti mosquito larvae with variation of extract concentration 50, 100, 250, 500, and 1000 ppm during 24 hours observation. Identification of compound content was done by testing the sample with GC-MS analysis. The results show that the yield of ethyl acetate extract equal to 1.86%. The LC value of this ethyl acetate extract was 105.79 ppm. The obtained LC50 values including active biolarvacidal groups and positive controls using abate had LC100 values at 100 ppm concentrations. Meanwhile, the LC50 value on granules using marsh Fleabane leaves extract content was obtained at 96.34ppm and LC90 was 905.1 ppm. The ability of active biolarvaside is corroborated by GC-MS analysis results indicating that the biolarvacid content of active compounds contained in ethyl acetate extract expected as quinic acid